2020
DOI: 10.3390/brainsci10020074
|View full text |Cite
|
Sign up to set email alerts
|

Validity and Reliability of a Test Battery to Assess Change of Directions with Ball Dribbling in Para-footballers with Cerebral Palsy

Abstract: The purpose of this study was to evaluate the content and construct validity and between-sessions reliability of four agility tests requiring ball dribbling in football players with cerebral palsy (CP) with implications for classification and training. A sample of 35 football players with CP from three different countries took part in the study. They performed four tests in two sessions 72 h apart: i) 20 m in a straight line, ii) forward slalom with short changes of direction, iii) forward slalom with wide cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
13
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 30 publications
0
13
0
4
Order By: Relevance
“…The choice of the present physical performance tests (Harre circuit test, Lower Quarter Y-balance test, and linear dribbling test) was based on their easiness, reliability [ 14 , 18 , 19 ], and enjoyability. Moreover, they can provide practical information on general motor coordination, dynamic balance, and dribbling skills.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The choice of the present physical performance tests (Harre circuit test, Lower Quarter Y-balance test, and linear dribbling test) was based on their easiness, reliability [ 14 , 18 , 19 ], and enjoyability. Moreover, they can provide practical information on general motor coordination, dynamic balance, and dribbling skills.…”
Section: Methodsmentioning
confidence: 99%
“…A linear dribbling test was employed to assess participants’ ability to rapidly dribble the ball [ 19 ]. The participants dribbled the ball down a corridor 1.5 m wide and 20 m long across two cones.…”
Section: Methodsmentioning
confidence: 99%
“…Evidence-based classification in CP football has already reported several tests to explore determining factors to discriminate between different sport classes and impairment severity (i.e., FT5/FT6/FT7 vs. FT8) and between minimum impairment and controls (i.e., FT8 vs. not eligible), according to abilities such as balance [ 14 ], coordination [ 2 , 15 ], horizontal and vertical jumps [ 16 ], change of direction [ 17 ], sprinting, accelerations and decelerations [ 18 ], and dribbling skills [ 19 ]. Recently, Reina et al [ 2 ] suggested that the relationship between activity limitation and sports performance should be considered impairment specific for para-athletes with HAA.…”
Section: Introductionmentioning
confidence: 99%
“…Football Cerebral Palsy (CP) is for disability classification. Para-athletes play football for individuals with CP football with minimal impairment criteria of ataxia, hypertonia, or athetosis (i.e., the three types of disorders most commonly associated with individuals with neurological disorders [6]. Cerebral Palsy football is a team sport in which players are classified in sports classes based on the extent to which cerebral motor control disorders lead to permanent and verifiable activity restrictions that affect football skills performance [7].…”
Section: Introductionmentioning
confidence: 99%